1992
DOI: 10.1021/jf00013a017
|View full text |Cite
|
Sign up to set email alerts
|

Nontoxicity of polar abamectin degradates from citrus fruit and thin film photolysis

Abstract: After application to crops, abamectin (avermectin BI, plus avermectin Bib) degrades largely to a polar residue of unknown identity. Such polar degradates are also formed after photolysis of abamectin as a thin film on glass for approximately 1 day. To establish the safety of these residues, polar abamectin degradates were isolated from oranges treated with abamectin in the field and after photolysis of thin films on glass. These degradates were tested and found to have no adverse maternal or developmental effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Such effect obtained under our experimental conditions can be explained that the amount of abamectin applied to each beaker had been degradated into other compounds which did not cause any significant clastogenic metaphases. Our results, are in accord to other results obtained by Crouch et al (1992 chromosomal aberrations which significantly decreased by the days following treatment until reached the least after 8 days of treatment. Also , abamectin was found to induce physiological type of aberrations.…”
Section: Cytotoxicity Of Abamectin Degradatessupporting
confidence: 93%
“…Such effect obtained under our experimental conditions can be explained that the amount of abamectin applied to each beaker had been degradated into other compounds which did not cause any significant clastogenic metaphases. Our results, are in accord to other results obtained by Crouch et al (1992 chromosomal aberrations which significantly decreased by the days following treatment until reached the least after 8 days of treatment. Also , abamectin was found to induce physiological type of aberrations.…”
Section: Cytotoxicity Of Abamectin Degradatessupporting
confidence: 93%
“…The various combinations possible with the known primary degradation reactions and the postulated C-O and C=C cleavages, therefore, could result in a very large number of compounds, such as oxygenated fragments of the macrocycle or ring-opened and oxygenated degradates of the macrocycle. Although little information is available regarding the end products of MAB1A photodegradation on glass, the very similar compound avermectin Bia does photodegrade on glass to a complex, polar residue (Crouch et al, 1991) that is comparable to that found in avermectin Bia-treated oranges (Crouch et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…photodegradation are the delta 8,9-isomer of avermectin B 1a and a polar and a moderately polar fraction, of which only the 8,9-isomer was found to be toxic 1,2 . Abamectin is the active ingredient found in formulations registered worldwide for control of motile mites and insect larvae on both agricultural and crops.…”
Section: Introductionmentioning
confidence: 99%